Pelaksanaan Pembelajaran Ranah Sikap Sosial PadaMata Pelajaran Pendidikan Pancasila DanKewarganegaraan(Studi Kasus Di Smk Pancasila 1 Wonogiri Tahun Pelajaran (2015-2016) - Wardani, Monika Putri Kusuma, Drs. Achmad Muthaliin, M.Si (2016)
The general objective of this study was to describe the realm of learning social attitudes on subjects Pancasila and Citizenship Education at SMK Pancasila 1 Wonogiri. This study is a qualitative research, with a case study strategy. Technique data collecting by observation, interviews, and documentation. Validity of the data using a triangulation of data sources and data collection techniques. Analysis of the data using interactive analysis techniques. The results of this study indicate that the implementation of learning the realm of social attitudes on subjects done by good behavior towards friends, teachers, and school environment, arrive on time and obey the order, do the tasks as determined, do not cheat or not to tell lies, usually with discussion, respect the opinion or religion, of expression for example in the question and answer. Constraints implementation of the social realm of learning is the lack of attitude of manners, many are ditching, most students are late collecting duties, there is a tradition of cheating, at the time of the discussion just a few working on, at the time of Ramadan there are packed, many students are inferior. The solution of these constraints by giving a good example of the teacher, the student's name is recorded on the books of the violation if disciplinary breaches, when students turn in assignments late then the value will be reduced, teachers should set an example to be honest to the students, with discussion of the students will be working and each written job descriptions groups, teachers should always remind their students to appreciate the differences, the teacher must always motivate children to appreciate differences.